The Effectiveness Of The Hydrotherapy Method With Warm Compresses To Reduce Pain In Active Phase Labor - Pratiwi Puji Lestari; Fika Aulia (MBUnivPress, 2023)
Labor pain is a natural thing but is used as a complaint by giving birth mothers. Labor pain causes pain due to the body releasing stress hormones. Excessive secretion of stress hormones will cause circulatory disorders, thereby inhibiting labor and causing fetal hypoxia. Hydrotherapy through warm compresses is a non-pharmacological method that is easy to do to reduce labor pain. The purpose of this study was to determine the effectiveness of the warm compress hydrotherapy method in reducing labor pain. The research method uses experimental quantitative analytic research with a post-test only control design. Analysis using t-test. The experimental and control group samples were taken randomly from the population. The results showed that the average respondent's pain before being given hydrotherapy was 7.00 with a standard deviation of 1.356, the average respondent's pain after being given hydrotherapy was 5.50 with a standard deviation of 1.364, there was a significant difference before and after applying warm compresses with p = 0.000 where p < 0 ,05. Conclusion: Hydrotherapy with warm compresses can reduce labor pain. Suggestion: health workers can provide warm compresses hydrotherapy to reduce labor pain so that it can reduce the morbidity rate for mothers in childbirth.